Realizing QVT with Graph Rewriting-Based Model Transformation - Lengyel, Laszlo; Levendovszky, Tihamér; Vajk, Tamás; Charaf, Hassan (Electronic Communications of the EASST, 2006)
Model-based development is an increasingly applied method in producing software artifacts that is driven by model transformation. For instance, OMG’s Model-Driven Architecture as a model-based approach to software development facilitates the synthesis of application programs from models created using customized, domain-specific model processors. Meta Object Facility 2.0 Query/ Views/ Transformation (QVT) is the OMG’s standard for specifying model queries, views, and transformations. Extensive research of graph transformation provides a strong formal background for model transformation. The main contribution of this paper is to show how high-level constraint constructs facilitate to realize transformations specified in QVT with metamodel-based model transformation. As a result we can reuse the graph transformation constructs, and its formal background, which facilitates to make QVT transformations validated.